Linguistic personality in mass media: scientific interpretation and characteristic features - Rudiuk, Liudmyla (Current issues of Ukrainian linguistics: theory and practice, 2020)
The article focuses on the necessity and appropriateness of scientific analysis of linguistic personality in mass communication as a separate subject of study, given the rapid development of mass media that produce a change in linguistic resource. In addition, the main approaches of researchers to the interpretation of the concept of "linguistic personality in media" were analyzed. An attempt was made to highlight the basic levels of communicative competence, characteristic features of the linguistic personality in media, taking into account the dominant tendencies of the development of mass communication sphere and the reorientation of the linguistic paradigm towards its intentional, communicative and functional component. In the scientific interpretation of the concept of "linguistic personality in media," the accentuation on multidimensional and polystructural dynamics of this concept, is indicative, which is characterized by the correlation of different analyzed parameters. The article focuses on representative criteria for highlighting a linguistic personality in media, attention is paid to cases where the linguistic personality is represented by both text publications and audio, video materials, and the syncretism of extra- and intralinguistic factors is important in the process of formation and functioning of the linguistic personality in media. One of the dominant categories for substantiating a linguistic personality in media is media discourse. Cases when media becomes a prism and a platform, where the linguistic personality becomes known and significant to the mass audience and when the linguistic personality is actually representative of the mass communication sphere were considered The idiocystology of the linguistic personality in media, the unique appeal and stylistic resource in speech, the normalization of linguistic characteristics make the texts and speeches of the linguistic personality in media significant because they have an impact on the society and are aimed at mass audience. On the example ofmedia texts of Yulia Mostova, a prominent linguistic personality in mass media, the editor-in-chief of the «Mirror of the Week» edition, linguistic and stylistic features, dominant linguistic markers (in particular, lexico-phraseological and syntactic features), their functional load were analyzed, which appropriate Yulia Mostova as a linguistic personality and make her texts creative and interesting for the recipients.